2014
DOI: 10.1002/bab.1156
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and ultrastructural studies of lignocellulose biodegradation during Agaricus bisporus cultivation

Abstract: During Agaricus bisporus cultivation, lignocellulose degradation is the result of the activity of both the mushroom and microbial communities developed during the composting. To investigate the lignocellulose degradation in detail from the beginning to the end of the process, the functional groups of cellulose, hemicellulose, and lignin have been studied with Fourier transform infrared spectroscopy and the morphological changes of lignocelluloses were elucidated with scanning electron microscopy. The aperture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In China, rice and corn straw are also used successfully. Rice straw is closer to wheat straw, while corn straw more resembles barley or oat straw and loses its texture more quickly 6,31,32 . Up till now, few studies on millet straw have been reported for both its physico-chemical properties and application on mushroom cultivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, rice and corn straw are also used successfully. Rice straw is closer to wheat straw, while corn straw more resembles barley or oat straw and loses its texture more quickly 6,31,32 . Up till now, few studies on millet straw have been reported for both its physico-chemical properties and application on mushroom cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…Fresh millet straw segments of different phases were randomly collected, fixated, dehydrated, replaced, dried, and covered with gold in an Emscope sputter coater (HITACHI E-1010, JPN). Subsequently, samples were examined using a scanning electron microscope (TESCAN TS 5136MM, CZE) 32,46 .…”
Section: Methodsmentioning
confidence: 99%